Leadership behaviour, entrepreneurial orientation and organisational performance in Malaysian small and medium enterprises - Azizah Hashim (2019)
The purpose of this study was to identify the leadership behaviour, entrepreneurialorientation and organisational performance of Small and Medium Enterprises (SMEs) in Malaysia.Three main constructs were selected namely leadership behaviour, entrepreneurial orientation andorganisational performance based on Resource Based Theory (RBT) by Galbreath (2005) andTransformational Leadership Theory by Bass (1985). The research design used in this study was asurvey method and data were collected using quantitative approaches. The respondents were 401 owneror manager of SMEs operating in manufacturing and service industries in Kuala Lumpur and Selangor.The respondents were selected using the Stratified Sampling Technique. The study instrument appliedwas questionnaires. The finding showed that transformational leadership has higher impact towardsorganisational performance (β=0.257, S.E=0.055) than transactional leadership (β=0.220, S.E=0.054).Entrepreneurial orientation also significantly contributed to organisational performance (β=0.199,S.E=0.054). Furthermore, this study found that entrepreneurial orientation acted as partialmediator between leadership behaviour and organisational performance (β=0.284, S.E= 0.256). The keyimplications of this study revealed that transformational leadership proved to be more efficientthan transactional leadership in term of leadership behaviour. Thus, the leader of SMEs need topractise and nurture the qualities of transformational leadership, and focus on entrepreneurialorientation in order to achieve better organisational performance. This study also acknowledges theleadership and entrepreneurial orientation as a resource and capability in organisation because theintegration of these two elements are the yardstick for SMEs’ success in Malaysia.